Cyberlaw and Identification: A Comprehensive Analysis of Journal Articles on Lens.org - Bagus Trispratama, Enrico; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article aims to provide a comprehensive overview of the landscape of journal articles related to Cyberlaw and Identification on Lens.org. The data was collected by using the keywords "Cyberlaw OR Cyber Law AND Identification" and filtering for journal articles in the subject of law. The results reveal a significant volume of articles, with the highest production in 2017, decreasing in recent years. The London School of Economics and Political Science stands out as a prominent institution, and the United Kingdom leads in authorship. Elsevier emerges as the top publisher, with a focus on topics like privacy and international cyber law. This data article sheds light on the global trends in Cyberlaw and Identification research, providing valuable insights for scholars and the public interested in this field. Highlights: Extensive Coverage: The data analysis revealed a wealth of journal articles on Cyberlaw and Identification, with a peak in 2017, offering a broad resource for researchers and scholars. Prominent Institutions: The London School of Economics and Political Science emerged as a leading contributor, underlining its significance in the field of Cyberlaw. Leading Trends: The United Kingdom took the lead in authorship, while Elsevier stood out as the dominant publisher, emphasizing the global importance of privacy and international cyber law research. Keywords: Cyberlaw, Identification, Journal Articles, Data Analysis, Global Trends